Emergency and Basic Life Support in Dentistry - Anggraini, Santi; Jamaluddin, Ahmad; Mohamad Amin, Norhayati binti (International Journal of Human and Health Sciences (IJHHS), 2025)
Dental emergencies represent a critical challenge requiring high preparedness, clinical competence, and an organized response system to prevent morbidity and mortality. This review aims to explore the prevalence of dental emergencies in Indonesia, highlighting epidemiological, systems-based management approaches, pharmacology, and medicolegal aspects. The findings indicate that the prevalence of dental emergencies continues to increase, along with changes in patient demographics, especially the elderly population with complex medical comorbidities, and advances in medical technology. Protocol-based approaches, such as the modified ABCDE for dentistry, have improved the effectiveness of emergency diagnosis and intervention. Integration of modern technologies, such as digital imaging and telemedicine, also accelerates clinical response. In addition, the implementation of a coordinated referral system and interdisciplinary collaboration have been shown to strengthen clinical outcomes. In the pharmacological realm, management of adverse reactions to local anesthetics and selection of safe anesthetic agents are top priorities to minimize the risk of complications. Medicolegal aspects also receive special attention, with a focus on the implementation of informed consent, comprehensive documentation, and risk management protocols to reduce litigation. This review article provides evidence-based recommendations to improve the quality of dental emergency management, including the need for ongoing education and training for dental practitioners. With a holistic, evidence-based approach and interdisciplinary collaboration, the impact of dental emergencies on patient health can be significantly minimized, improving the standard of dental care in Indonesia. International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 93-101